Changing Lengths of the Four Seasons by Global Warming - Jiamin Wang; Yuping Guan; Lixin Wu; Xiaodan Guan; Wenju Cai; Jianping Huang; Wenjie Dong; Banglin Zhang (Geophysical Research Letters)
Abstract How long will the four seasons be by 2100? Increasing evidence suggests that the length of a single season or in regional scales has changed under global warming, but a hemispherical‐scale response of the four seasons in the past and future remains unknown. We find that summer in the Northern Hemisphere midlatitudes has lengthened, whereas winter has shortened, owing to shifts in their onsets and withdrawals, accompanied by shorter spring and autumn. Such changes in lengths and onsets can be mainly attributed to greenhouse‐warming. Even if the current warming rate does not accelerate, changes in seasons will still be exacerbated in the future. Under the business‐as‐usual scenario, summer is projected to last nearly half a year, but winter less than 2 months by 2100. The changing seasonal clock signifies disturbed agriculture seasons and rhythm of species activities, more frequent heat waves, storms and wildfires, amounting to increased risks to humanity.